High-pressure liquid chromatography (HPLC) pigment concentration data and flow-cytometry picophytoplankton abundance and fluorescence data from depth-resolved CTD profiles at 'Biomass stations' during RV Tangaroa expedition TAN1702 - Gutiérrez-Rodríguez, Andrés; Latasa, Mikel; Safi, Karl; Pinkerton, Matt; Nodder, Scott D (In: Gutiérrez-Rodríguez, A et al. (2023): Phytoplankton taxon-specific growth and microzooplankton grazing rates in subantarctic HNLC waters on and off Campbell Plateau southeast of New Zealand during austral autumn [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.958525, 2023)
Here we present data of phytoplankton pigment and flow cytometry (FCM) depth-resolved data collected from the water column (0-100 m) during TAN1702 voyage (March-April 2017) in subantarctic waters across the Campbell Plateau region southeast of New Zealand on board of the RV Tangaroa.
Keywords: diatoms; Ecumenical hypothesis; HNLC subantarctic; Microzooplankton grazing; Phytoplankton growth; prasinophytes